Perkembangan Hukum Islam Pada Masa Khalifah Abdul Malik Bin Marwan - Syafri Gunawan (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2022)
This article discusses the progress of Islamic law during the caliphate Abdul Malik bin Marwan who was one of the Umayyad caliphs in Syria who was firm and longest in power, with a fairly long period, so of course there were many breakthroughs as caliphs in advancing the Islamic kingdom at that time. , including developing Islamic law.The method used in this article is a qualitative method, here the author seeks from various literatures that review the caliphate of Abdul Malik bin Marwan which then the author analyzes to answer questions about the development of Islamic law during the caliphate of Abdul Malik bin Marwan descriptively.The finding that during the caliphate of Abdullah bin Marwan there has been a fantastic development of Islamic law, namely the establishment of the High Court to try officials who deviate or act arbitrarily against the people, so it is noted that during his caliphate Queen Kahina as the leader of the Barbarians was sentenced to death.